Behavioral and electrophysiological responses of Hippodamia variegata to plant volatiles - Yi Wang; Ying Zhang; Tao Zhang; Zihan Li; Tinghui Liu; Yanhui Lu (PLoS ONE, 2025)
Natural enemies use odors to find prey in nature. The use of plant volatiles to attract natural enemy insects and promote their feeding on pests has great potential for practical application in integrated pest management. Of the 28 materials tested, ethyl benzoate, octyl formate, methyl jasmonate, and methyl dihydrojasmonate were significantly attractive to H. variegata. We tested the ladybeetle’s behavioral responses to three concentrations of the compounds (100, 10, and 1 µg/µL) and found that high and medium levels were both attractive to H. variegata. In electroantennography (EAG) tests, the response of H. variegata to the above four compounds increased with the increasing concentration. Also, feeding of H. variegata increased in the presence of these plant volatiles under the condition of enclosures. These findings provide a theoretical basis for future behavioral manipulation of this predator under field conditions.